Physical Fitness Level of Female Futsal Athletes at STKIP JB Angels Club - Yully Wahyu Sulistyo; Aditya Harja Nenggar (Universitas Majalengka, 2023)
Futsal is a team sport that relies on high-intensity, intermittent activities that require athletes with excellent physical fitness. Optimal fitness condition (VO2Max) is the main capital for every futsal athlete in order to fully concentrate and work optimally from the beginning to the end of the match. purpose of knowing the level of physical fitness of STKIPJb Angles Club futsal athletes. Descriptive quantitative research method, with a total sample of 12 female athletes who are members of the STKIPJB Angles Futsal club, athletes' physical fitness is measured using the MFT test, data analyzed by descriptive quantitative. AthletesÂ who have VO2Max conditions with excellent categories amounted to 2 (16.7%), good 2 athletes (16.7%), enough 5 athletes (41.6%), less 3 athletes (25%), while the category is very less than 0 (0%). Most athletes' physical fitness is in the moderate category, so suggestions for coaches to be able to develop training programmes that can improve the fitness (VO2Max) of futsal athletes This is because futsal is a team sport that relies on high-intensity intermittent activity, so it requires athletes with excellent physical fitness. Further studies are needed to determine the factors that cause low physical fitness and provide effective exercises to improve athletes' physical fitness.